Analisis UX pada Aplikasi Pemutar Video Animasi dengan Metode Usability Testing - I Gusti Ngurah Esa Nandana; I Gede Arta Wibawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
A popular animation streaming platform requires a structured User Experience (UX) evaluation to ensure its ease of use. This study aims to analyze the usability level of an animation video player application using a mixed-method Usability Testing approach. The test was conducted on 5 active users, where performance data (success rate, time efficiency, error rate) and perceptual data (satisfaction level) were collected through task-based observation sessions and a post-test questionnaire. The results indicate a perfect task success rate (100%) and a high user satisfaction level (88%), but also reveal a significant error rate of 60%. The primary source of errors was identified as the ambiguity of iconography without text labels on certain features. In conclusion, the application is proven to be functional and satisfying, but it is recommended to improve the clarity of the interface design to minimize user errors and enhance the overall UX.